A Two-Way Proteome Microarray Strategy to Identify Novel Mycobacterium tuberculosis-Human Interactors - Tingming Cao; Lingna Lyu; Hongyan Jia; Jinghui Wang; Fengjiao Du; Liping Pan; Zihui Li; Aiying Xing; Jing Xiao; Yu Ma; Zongde Zhang (Frontiers in Cellular and Infection Microbiology, 2019)
Tuberculosis (TB) is still a serious threat to human health which is caused by mycobacterium tuberculosis (Mtb). The main reason for failure to eliminate TB is lack of clearly understanding the molecular mechanism of Mtb pathogenesis. Determining human Mtb-interacting proteins enables us to characterize the mechanism and identify potential molecular targets for TB diagnosis and treatment. However, experimentally systematic Mtb interactors are not readily available. In this study, we performed an unbiased, comprehensive two-way proteome microarray based approach to systematically screen global human Mtb interactors and determine the binding partners of Mtb effectors. Our results, for the first time, screened 84 potential human Mtb interactors. Bioinformatic analysis further highlighted these protein candidates might engage in a wide range of cellular functions such as activation of DNA endogenous promoters, transcription of DNA/RNA and necrosis, as well as immune-related signaling pathways. Then, using Mtb proteome microarray followed His tagged pull-down assay and Co-IP, we identified one interacting partner (Rv0577) for the protein candidate NRF1 and three binding partners (Rv0577, Rv2117, Rv2423) for SMAD2, respectively. This study gives new insights into the profile of global Mtb interactors potentially involved in Mtb pathogenesis and demonstrates a powerful strategy in the discovery of Mtb effectors.